2018
DOI: 10.1021/acsami.8b15946
|View full text |Cite
|
Sign up to set email alerts
|

Design Strategy for the Controlled Generation of Cationic Frameworks and Ensuing Anion-Exchange Capabilities

Abstract: Cationic frameworks are an emerging class of exceptional solid adsorbents capable of encapsulating highly toxic and persistent anionic pollutants. The controlled generation of cationic frameworks, however, lags behind the abundant design strategies devised to control the structures and topologies of neutral frameworks. In this regard, we report a rational approach that allows the conversion of the synthetic approach toward constructing a neutral framework into one allowing for the synthesis of a cationic one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…We further studied the effects of different anions, as chemical properties and geometry of these anions dictate their spatial arrangement in the pacs system [16] . Prior to gas sorption studies, we confirmed phase purity of Co 3 ‐cpt‐tph‐x (x=Cl − , Br − , ClO 4 − , BF 4 − ) by comparing their powder X‐ray diffraction (PXRD) with simulated ones (Figure S4).…”
Section: Resultsmentioning
confidence: 90%
“…We further studied the effects of different anions, as chemical properties and geometry of these anions dictate their spatial arrangement in the pacs system [16] . Prior to gas sorption studies, we confirmed phase purity of Co 3 ‐cpt‐tph‐x (x=Cl − , Br − , ClO 4 − , BF 4 − ) by comparing their powder X‐ray diffraction (PXRD) with simulated ones (Figure S4).…”
Section: Resultsmentioning
confidence: 90%
“…There are numerous examples of postsynthetic exchange of charge-balancing anions residing within the pores of cationic MOFs. However, inner-sphere, postsynthetic X-type ligand exchange (PXLE) at MOF metal nodes has been less studied, partly as a result of the relative paucity of materials containing exchangeable X-type ligands. Hupp and co-workers pioneered solvent-assisted ligand incorporation (SALI) as a means of immobilizing nonstructural carboxylate or phosphonate groups at linker-deficient 6- or 8-connected Zr 6 nodes (Figure a) .…”
Section: Introductionmentioning
confidence: 99%
“…One common approach relies on the introduction of well-studied catalytically active guest species within the channels or cages of MOFs, enabling highly efficient reactions. , In this regard, positively or negatively charged MOFs have the advantage of allowing a straightforward and efficient inclusion of anionic or cationic metal complexes with well-defined catalytic behaviors through ion-metathesis reactions. The exchange of noncoordinating ions in MOFs has previously been shown to impact a number of physical properties, including gas adsorption behaviors and proton conductivity. Thus far, however, tuning the catalytic performance of a charged MOF via replacement of nonactive ionic guest species has yet to be reported.…”
Section: Introductionmentioning
confidence: 99%